2007
DOI: 10.1080/10408360601003143
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Markers In Biological Fluids Associated With Pregnancy

Abstract: Proteins that are expressed by both malignant and healthy fetal tissues are recognized as oncofetal. These antigens are associated with cell proliferation and differentiation and are produced in high concentrations in pregnancy and malignancy. Their biological role in malignancy is the suppression of the host's immune system, while in pregnancy they affect the maternal immune response, generating maternal tolerance toward the embryo. This review describes the levels of alpha-fetoprotein (AFP), human chorionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 131 publications
2
84
0
12
Order By: Relevance
“…These markers have previously been investigated in the biologic fluids of healthy pregnant and non-pregnant women. The presence of considerable concentrations of tumor markers during pregnancy may be attributed to their involvement in biological functions associated with fetal development, differentiation, and maturation [19]. One of these tumor markers, CA 19-9, is mostly used as a serum marker for malignancies, but it is also present in the serum and amniotic fluid of pregnant women [20].…”
Section: Discussionmentioning
confidence: 99%
“…These markers have previously been investigated in the biologic fluids of healthy pregnant and non-pregnant women. The presence of considerable concentrations of tumor markers during pregnancy may be attributed to their involvement in biological functions associated with fetal development, differentiation, and maturation [19]. One of these tumor markers, CA 19-9, is mostly used as a serum marker for malignancies, but it is also present in the serum and amniotic fluid of pregnant women [20].…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicated that HE4 may remain as a robust marker of ovarian cancer during pregnancy following certain adjustment. Since several other markers such as CA125 and alpha fetoprotein (AFP) tend to be elevated during pregnancy [47], HE4 could be a valuable maker to guide the triage of patients with ovarian cysts and pelvic masses in the setting of pregnancy.…”
Section: He4 Levels In Female Reproductive Cyclesmentioning
confidence: 99%
“…It is elevated in nonovarian carcinoma, including fallopian tube, endometrium, endocervix, pancreas, colon, stomach, gall bladder, kidney, mesothelial lining of pleura, pericardium, apocrine sweat gland etc [4]. It is also elevated in follicular phase of menstrual cycle, those with benign conditions such as cirrhosis, hepatitis, endometriosis, Pericarditis and early pregnancy [5,6]. We had taken preoperative serum values of CA125 of patients with ovarian tumors and compared with CA125 expression in imprint cytology and tissues.…”
Section: Introductionmentioning
confidence: 99%